Volume Estimation of Lung Cancer using Image-J For CT-Scan Image - Nurjannah Nurjannah; Syarifah Zainura; Edwar Iswardy; Elin Yusibani (Department of Physics, Sebelas Maret University, 2024)
ABSTRACTLung cancer is a malignant tumor that develops in the lower respiratory system, including cells in the walls of the bronchi and bronchioles. Lung cancer originates from genetic changes in cells in the lungs. Improper treatment of lung cancer can cause the cancer to spread to other nearby tissues around the lungs. By conducting early detection of lung cancer, it will help patients to get appropriate treatment. One of the medical instruments used to detect lung cancer is the CT-Scan. This instrument’s examination can provide information about the location, size, characteristics of the tumor, lymph node spread, and tissue infiltration into the surroundings, thus helping to determine the clinical stage of lung cancer. Organ size determination is one of the analysis of pulmonary image for diagnostic and therapeutic purposes. The purpose of this study was to obtain information on the volume of lung cancer based on the results of CT Scan images using Image J software. Information on the edges of the lungs affected by cancer was carried out by the edge detection method. The results of this study show that Image-J software can provide a clear picture of the edges of the cancer and obtain accurate cancer volume at each image slice. Based on calculations obtained in the 1st patient, it was calculated to have a volume of 128 cm3, in the 2nd patient of 447 cm3 and in the 3rd patient of 335 cm3, respectively.Keywords: Ct Scan image; lung cancer; edge detection; volume analysis; Image JABSTRAKKanker paru merupakan tumor ganas yang berkembang pada sistem pernapasan bagian bawah, termasuk sel-sel di dinding bronkus dan bronkiolus. Kanker paru berawal dari perubahan genetik sel di dalam paru-paru. Penanganan kanker paru yang tidak tepat dapat menyebabkan kanker menyebar ke jaringan lain yang terdekat di sekitar paru-paru. Dengan dilakukan pendeteksian dini kanker paru, maka akan sangat membantu penderita agar mendapatkan penanganan yang cepat dan tepat. Salah satu instrumen medis yang digunakan untuk mendeteksi kanker paru adalah pesawat CT-Scan. Pemeriksaan CT-Scan dapat memberikan informasi tentang lokasi, ukuran, karakteristik tumor, penyebaran kelenjar getah bening, dan infiltrasi jaringan ke sekitarnya sehingga membantu penetapan stadium klinis kanker paru. Penentuan ukuran organ merupakan salah satu analisa terhadap citra paru untuk keperluan diagnosa dan terapi. Tujuan penelitian ini adalah memperoleh informasi volume kanker paru berdasarkan hasil citra CT Scan menggunakan Image J. Informasi gambaran tepi paru yang terkena kanker dilakukan dengan metode deteksi tepi. Hasil dari penelitian ini menunjukan bahwa software Image-J dapat memberikan gambaran tepi kanker yang jelas dan diperoleh volume kanker yang akurat pada setiap irisan citra. Berdasarkan perhitungan didapatkan pada pasien ke-1 terhitung memiliki volume sebesar 128 cm3, pada pasien ke-2 sebesar 447 cm3 dan pada pasien ke-3 sebesar 335 cm3.Kata kunci: CT Scan; Kanker paru; deteksi tepi; analisis volume; Image J